WASTEWATER TREATMENT OF AN OIL REFINERY BY ADVANCED OXIDATION (AOX), USING FENTON REAGENT (H2O2/Fe^(2+)) - Salas C., Gilberto (2008)
In this paper we evaluate the technical feasibility of advanced oxidation process (AOX) using the reagent Fenton H2O2/Fe^(2+) in the treatment of wastewater generated by the caustic washing of an oil refinery. These waters contain a chemical oxygen demand (DQO), 20 160 mg / L and total phenols 1 800 mg / L. The results show the treatment efficiency of removal of 90% for DQO, and 99% for total phenol at pH 4.